2016
DOI: 10.3892/or.2016.5127
|View full text |Cite
|
Sign up to set email alerts
|

Depression accelerates the development of gastric cancer through reactive oxygen species-activated ABL1 (Review)

Abstract: Depression is a common symptom among gastric cancer (GC) patients and serves as a potential indication of poor prognosis and advanced cancer clinical stage. However, the molecular mechanism of depression‑associated poor prognoses of GC patients remains unclear. Recent studies have revealed that GC patients with depression are under high levels of oxidative stress (OS) status that is accompanied by the dysfunction of numerous proto‑oncogenes, including the ABL proto‑oncogene 1 (ABL1), which is a non‑receptor ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 86 publications
(105 reference statements)
0
23
0
Order By: Relevance
“…Control subjects were individually selected from the same residence town of matched case patient or from the town with similar incidence of GC , matching for sex and age (±3 years). We divided Xianyou County into three groups of region (high, middle, and low incidence area) based on the standardized mortality rate of GC that was reported in our previously study (Huang et al, 2016). Eligible controls must have also been resided in Xianyou County for at least 10 years and haven't been diagnosed with GC.…”
Section: Study Design and Study Populationmentioning
confidence: 99%
“…Control subjects were individually selected from the same residence town of matched case patient or from the town with similar incidence of GC , matching for sex and age (±3 years). We divided Xianyou County into three groups of region (high, middle, and low incidence area) based on the standardized mortality rate of GC that was reported in our previously study (Huang et al, 2016). Eligible controls must have also been resided in Xianyou County for at least 10 years and haven't been diagnosed with GC.…”
Section: Study Design and Study Populationmentioning
confidence: 99%
“…ABL1 is indirectly activated by fumarate, promotes aerobic glycolysis via activation of the mTOR-HIF1α pathway, and induces NRF2 transcription/activity, which protects cells from ROS-induced injury [73]. Moreover, ABL1 has been postulated to mediate gastric cancer development following activation by depression-induced oxidative stress [74]. Consistent with the above reports, multiple metabolic pathway genes that regulate energy metabolism are altered in MCF-7 cells expressing ABL1/ABL2-targeted siRNA [75].…”
Section: Abl Kinases Regulate Tumor Growthmentioning
confidence: 99%
“…Although several studies have demonstrated that deletion of ABL1 causes spermatogenic failure (Kharbanda et al, ), the role of ABL1 upregulation in spermatogenesis remains unclear. ABL1 has recently been reported to be activated by ROS (Huang, Zhou, Wang‐Johanning, Nan, & Wei, ), and upregulation of ABL1 promotes p53 transcriptional activity (Furlan et al, ). In addition, ABL1 is essential for the regulation of the cytoskeleton (Bradley & Koleske, ), and the cytoskeleton is vital for the transport, mitosis and meiosis of germ cells (Su, Mruk, & Cheng, ; Wen et al, ).…”
Section: Discussionmentioning
confidence: 99%